2009
DOI: 10.1089/ten.tea.2009.0011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Collagen Crosslinking in Differentiation of Human Mesenchymal Stem Cells and MC3T3-E1 Cells

Abstract: Collagen is the main protein component of the extracellular matrix of bone, and it has structural and instructive properties. Collagen undergoes many post-translational modifications, including extensive crosslinking. Although defective crosslinking has been implicated in human syndromes (e.g., osteogenesis imperfecta or Ehlers-Danlos syndrome), it is not clear to what extent crosslinking is necessary for collagen's instructive properties during bone formation. Here we report that inhibition of collagen crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 62 publications
3
37
2
Order By: Relevance
“…Our findings reveal that Lox inhibition promotes BMP4‐induced osteogenesis, which contradicts previous reports about the functions of Lox in bone development 14, 42, 43, 44. Specifically, primary calvarial osteoblasts from Lox −/− mice exhibit decreased osteoblastic differentiation,14 and BAPN inhibits osteoblastic differentiation of MC3T3‐E1 preosteoblasts 44, 45. This discrepancy may be owing to the presence of BMP4, a molecule with both pro‐adipogenic and pro‐osteogenic effect, in that BAPN alone inhibited osteogenesis both in vitro (Figure S1) and in vivo (Figure S5), which was consistent with the previous study that Lox inhibit osteoblast differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings reveal that Lox inhibition promotes BMP4‐induced osteogenesis, which contradicts previous reports about the functions of Lox in bone development 14, 42, 43, 44. Specifically, primary calvarial osteoblasts from Lox −/− mice exhibit decreased osteoblastic differentiation,14 and BAPN inhibits osteoblastic differentiation of MC3T3‐E1 preosteoblasts 44, 45. This discrepancy may be owing to the presence of BMP4, a molecule with both pro‐adipogenic and pro‐osteogenic effect, in that BAPN alone inhibited osteogenesis both in vitro (Figure S1) and in vivo (Figure S5), which was consistent with the previous study that Lox inhibit osteoblast differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, altered collagen cross-linking is frequently observed in aging and many systemic diseases [33,48,49] due to inappropriate post-translational modifications of collagen. It has been reported that impaired cross-linking in collagenous matrix affects osteoblast differentiation [70,71], indicating that collagen cross-linking also affects tissue turnover, which is another important determinant of bone quality. Therefore, the quantification and characterization of collagen cross-linking in bone may be useful for the diagnosis and understanding of bone status.…”
Section: Collagen Cross-linkingmentioning
confidence: 99%
“…55,56 Similar effects have also been seen in collagen gels. 57 In the present study, we hypothesized that bone formation within a critical-sized defect would be enhanced using uncultured bmMNCs encapsulated in fibrin gels for delivery of the cells within model scaffolds made of poly(L-lactic acid) (PLLA) or coralline hydroxyapatite (HA). Scaffold properties were also expected to play a significant role on bone formation.…”
Section: Introductionmentioning
confidence: 99%